Nootkatone mitigates LPS-induced acute lung injury by modulating the NF-κB and Nrf2 pathways in mice - Hanuman, D. D. V.; Banothu, Anil Kumar; Bharani, Kala Kumar; Yadala, Ravi Kumar; Khurana, Amit; Gadige, Ambica; Gandham, Nagarjuna (Frontiers in Veterinary Science, 2025)
Acute lung injury is a serious condition that can be life-threatening. Nootkatone, a promising phytochemical, possesses notable antioxidant and anti-inflammatory properties. The current study aimed to investigate the anti-inflammatory effects of nootkatone both in vitro using Raw 264.7 macrophages and in vivo through intraperitoneal administration at doses of 50 and 100 mg/kg for 7 days. Animals were divided into five groups: normal control (NC), disease control (DC; LPS 10 μg/kg, oropharyngeal), nootkatone low dose (NLD; 50 mg/kg, i.p. for 7 days + LPS), nootkatone high dose (NHD; 100 mg/kg, i.p. for 7 days + LPS), and nootkatone per se (NPS; 100 mg/kg nootkatone alone). The study assessed the efficacy of nootkatone against lipopolysaccharide (LPS)-induced lung injury in mice, with LPS administered via the oropharyngeal route at 10 μg/kg. Concentrations of nootkatone up to 50 μM were found to be safe, showing only a modest reduction in cell viability. Treatment with various doses of nootkatone effectively mitigated LPS-induced inflammation in Raw 264.7 macrophage cells, as indicated by modulation of inflammatory cytokines such as IL-10 and TNF-α. We observed significant (p < 0.05) alteration in absolute and relative lung weights, as well as in hematological profiles. The levels of cytokines (IL-6, TNF-α, IL-1β, IL-22; IL-17; IFN-γ; TGF-β1, and IL-10) were significantly modulated in the NLD (50 mg/kg) and NHD (100 mg/kg) groups. Furthermore, the levels of malondialdehyde and nitrite were significantly lower in these groups compared to the disease control. Histological analysis revealed the reversal of lung tissue damage in the treated group compared to the disease control group. Notably, immunohistochemical evaluation of Nrf-2, NF-κB, TNF-α, and COX-2 expression further confirmed the potent anti-inflammatory effects of nootkatone. This study provides comprehensive evidence that nootkatone may represent a promising candidate for further research in the management of pulmonary inflammation.